Julien Duvivier's Pépé le Moko - La Barthe, Henri 1887-1963; Scotto, Vincent 1876-1952; Yguerbouchen, Mohamed 1907-1966 (<<The>> Criterion Coll., 2003)
The notorious Pépé le Moko is a wanted man--women long for him, rivals hope to destroy him and the law is breathing down his neck at every turn. On the lam in the Casbah of Algiers, Pépé is safe from the police until a Parisian playgirl compels him to risk his life and leave its confines once and for all.
1.33:1 aspect ratio, 16:9 widescreen. - New, restored high-definition digital transfer from the extensive 35mm restoration
Orig.: Frankreich 1937
Enth. 1962 French television interview with director Julien Duvivier ; excerpts from the 1978 television documentary "Remembering Jean Gabin" ; excerpts from Ginette Vincendeau's BFI Classics study of "Pépé le Moko", addressing the historical background of the film's setting and the French crime novel genre ; a study of the lasting influence of "Pépé" on popular culture, including a special video comparison between "Pépé" and the 1938 U.S. remake "Algiers" ; essay by film critic Michael Atkinson
Keywords: Ashelbe -- Film and video adaptations; Fugitifs de justice - Algérie - Alger - Drame; Fugitives from justice -- Algeria -- Algiers -- Drama; Algerien; Kasbah (Algiers) -- Drama; Feature films; Fiction films; Film adaptations; Video recordings for the hearing impaired; Feature films - France; Foreign language films - French